Revealing the biocultural importance of Moringa oleifera (Moringaceae) in three villages, Kediri District, Indonesia - WHISNU FEBRY AFRIANTO; ARYA ARISMAYA METANANDA (Society for Indonesian Biodiversity, 2023)
Abstract. Afrianto WF, Metananda AA. 2023. Revealing the biocultural importance of Moringa oleifera (Moringaceae) in three villages, Kediri District, Indonesia. Biodiversitas 24: 6942-6952. Moringa oleifera Lam. (Moringaceae) is a multi-purpose species with significant use and cultural importance. However, communities have yet to cultivate and use this plant intensively. This study aims to identify the biocultural importance of M. oleifera by the communities in Kediri District, East Java, Indonesia. The qualitative and quantitative ethnobotanical approach was carried out in three villages, namely Datengan, Cerme, and Ngablak Villages, Kediri District, East Java. Data were collected based on a survey of 60 informants through a semi-structured study, direct field observation, and in-depth interviews that were selected using snowball sampling. The results showed that M. oleifera has a score ICI of 20.19 and a UV score of 3. This plant has long been grown or grows naturally at all research locations. This plant was utilized for food, medicines, fooder feed, rituals, live fence, firewood, and most importantly, the leaves. This plant can grow in a variety of environmental circumstances and managed agroecosystem land, but it has yet to be actively grown. However, local knowledge of M. oleifera has declined, particularly among younger generations. The reason for this is that this plant species is less economically important than other agricultural goods. This M. oleifera study demonstrates the value of the cultural keystone species paradigm in landscape appraisal for conservation efforts.